CORPO-DS: A tool to support decision making for component reuse through profiling with ontologies - Loumakos, Savvas; Andreou, Andreas S. (My University, 2016)
This paper introduces a software tool that supports the activities of a novel, reuse-based development framework, which focuses on assessing the suitability level of candidate components. The tool enables the creation of a specifications profile using a semi-formal natural language, which describes the desired functional and non-functional properties of the component(s) sought. It also offers the means to parse the profile automatically and translate it into instance values of a dedicated CBSE ontology. Finally, the tool performs matching between required and offered component properties at the level of ontology items and suggests the most suitable components to consider for integration based on a suitability ratio calculated.
Keywords: Components; Decision-Support; Matching; Reuse; Software tool